Certification Regimes in the Global Agro-Food System and the Transformation of the Nature-Society Relationship: Ecological Modernization or Modernization of Ecology?. Issue 1 (1st March 2022) - Saidul Islam, Md
Abstract: Recent years have witnessed a proliferation of environmental certification regimes in the global agro-food system—a trend characterized as an example of the ecological modernization approach—which emerged largely because of the rise of consumer sovereignty and the neoliberal push for environmental and social "quality" in food production and processing. Based on a robust analysis of global aquaculture, the article argues that the environmental certification regimes privilege some actors, species, and cultures while marginalizing others. While the fundamental tenet of the ecological modernization approach is to shape capitalism by ecological principles, I argue instead that through environmental certification, ecology or nature itself is largely shaped, transformed and restructured to fit into and thereby serve neoliberal global governance and accumulation in a normalized manner. The example of certification regimes is therefore more like a "modernization of ecology" rather than ecological modernization.